Scientific Clinical Trial Publication Productivity in Medical Oncology: A Comparative Analysis and Data Review of Northern and Southern Italy - Vittorio Gebbia; Sergio Rizzo; Dario Piazza; Daniela Sambataro; Giuseppa Scandurra; Maria Rosaria Valerio (Clinics and Practice, 2026)
Background: Italy exhibits a socioeconomic divide between its northern and southern regions, which extends into healthcare delivery and biomedical research. Medical oncology is particularly affected by this structural imbalance. This paper examines geographic disparities in clinical trial scientific publication output, citation impact, research funding, and collaboration networks in medical oncology between northern and southern Italy. Methods: A narrative bibliometric analysis was conducted using data from PubMed and other institutional databases of Italian Scientific Institutes for Hospitalization and Care. Data from the Italian National Agency for the Evaluation of Universities and Research Institutes, the Alliance Against Cancer, and the Italian Association for Cancer Research were also reviewed. Regional output was compared across two macro-areas, namely north and south Italy. Results: Northern Italian institutions account for a disproportionate share of publications, high-impact citations, and funded research projects. Northern Italy produces an estimated four to six times more medical oncology papers than southern Italy, driven by a higher concentration of cancer institutes, better-funded university hospitals, and stronger multidisciplinary infrastructure than in the south. Clinical trial density is highest in the north compared to the south (0.53 versus 0.02 per 100,000 inhabitants). Conclusions: The north–south divide in Italian oncology research productivity is real, multi-factorial, and persistent. The analysis reveals a substantial gap in research productivity, institutional capacity, and access to clinical trials between the two macro-regions. Targeted policy interventions, including decentralized trial models, dedicated funding streams for southern institutions, and stronger infrastructure for inter-regional collaboration, are urgently needed to ensure representativeness in oncology evidence generation and equitable scientific progress.